Antioxidant effect of various rosemary (Rosmarinus officinalis L.) clones - Stefanovits-Bányai, Éva (Acta Biologica Szegediensis, 2003)
The antioxidant effects, the levels of total phenol and the total phenol contents of volatile oils and plant extracts were determined in eight various Rosemary (Rosmarinus officinalis L.) clones. Antioxidant acitvities and the total phenol contents were measured by spectophotometric method as well as the volatile oil content of the fresh plants with gas chromatograph. Our preliminary results clearly indicate that the antioxidant capacity of volatile oils and plant extracts closely related to the total phenol contents. Reason of the observed differences should be revealed by the determination of the quantity and quality of the individual volatile oil components.